Ultrasonographic features of gallbladder wall thickening in dogs with hypoalbuminemia - Masahiro Murakami; Hock Gan Heng; Sarah Steinbach; Mario Sola (Veterinary Quarterly, 2023)
AbstractHypoalbuminemia has been considered as a cause of gallbladder wall thickening in humans and dogs. Recent study revealed that gallbladder wall thickening in dogs with hypoalbuminemia may not be associated with serum albumin/plasma levels within 48 h of ultrasound study. However, gallbladder wall edema may change within 48 h, and the ultrasonographic features of gallbladder wall thickening in dogs with hypoalbuminemia have not been reported. The purpose of this study is to describe the relationship between serum albumin levels within 24 h of ultrasound and gallbladder wall thickening, and to describe the ultrasonographic features of thickened gallbladder walls in dogs with hypoalbuminemia. 37 hypoalbuminemic dogs with gallbladder ultrasound images were retrospectively included. Ultrasound studies were reviewed, and gallbladder wall thickness, layering appearance, echogenicity, echotexture, distribution, evidence of gallbladder mucocele, and presence of peritoneal effusion were recorded. Additionally, serum albumin levels within 24 h of ultrasound study and the administerd sedation were recorded. The prevalence of gallbladder wall thickening in dogs with hypoalbuminemia was 13.5%. The 3-layer appearance of the gallbladder wall was observed in 4 dogs, and a single-layer gallbladder wall thickening in one dog. Diffuse thickening was observed in all 5 dogs. The serum albumin level of dogs with gallbladder wall thickening was not different (p = 0.14) from dogs without thickening. Gallbladder wall thickening was not common, occurring only with mild hypoalbuminemia, and was commonly associated with a 3-layer appearance and considered as gallbladder wall subserosal edema. Causes other than hypoalbuminemia may be responsible for thickening of the gallbladder wall in dogs with hypoalbuminemia.